Developing A Business Plan for Micro Powdered Spice Enterprises - Attamimi, Muniroh; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to design a comprehensive business plan for Herbi, a micro-enterprise producing powdered Indonesian spices, to address challenges in production, marketing, finance, and operations and support business growth. Design/Methodology/Approach – This study employs a descriptive qualitative research method. Data were collected through observation, interviews, and literature review. A purposive sampling technique was used to select six informants, including customers, potential customers, and owners of similarly scaled spice businesses in Malang, East Java. Findings – The results reveal that the absence of structured business planning has caused inefficiencies and reactive decision-making at Herbi. The proposed business strategy includes product development, distribution channel optimization, digital tool integration, and structured financial and organizational planning. The formulated business plan demonstrates investment feasibility potential and improvements in operational effectiveness. Originality/Value This study provides a practical and context-specific business planning model for powdered spice micro-enterprises, an area rarely explored in prior research. The proposed strategies offer actionable guidance for improving operations, financial management, and market readiness, serving as a valuable reference for similar small businesses.